Transformasi Pendidikan Di Masa Pandemi: Pelatihan Hybrid Learning Di SMK Cendikia Kota Cirebon - Raditya Danar Dana; Nana Suarna; Willy Prihartono (CV. Multi Kreasi Media, 2022)
The COVID-19 pandemic has changed the educational paradigm globally, presenting major challenges for educational institutions throughout the world. Cendikia Vocational High School (SMK) in Cirebon City is no exception. This research aims to provide an in-depth analysis of the situation at Cendikia Vocational School, Cirebon City during the COVID-19 pandemic, especially related to the implementation of Hybrid Learning Training (Darmin et al., 2022). In this analysis, we will explore partner locations and cases that have occurred, social and cultural aspects that influence education, specific problems faced, methods or approaches used in community service, and the implications of the results of this service. The results of community service, the COVID-19 pandemic has forced the education sector to adapt and evolve quickly. One significant response was the introduction of a hybrid learning system at Cendikia Vocational School, Cirebon City. By combining online and face-to-face learning, this approach allows students to remain involved in the learning process even in limited situations. The results of this Hybrid Learning training show that this learning method is able to meet students' needs effectively. Students experience increases in active engagement, ability to adapt to technology, and independent learning skills. Apart from that, educators also reported that they were able to provide material in a more structured and interactive manner. The experience of implementing Hybrid Learning at Cendikia Vocational School, Cirebon City provides valuable insight for the education sector in the future. This shows that despite major challenges such as the pandemic, innovation and adaptation are key to ensuring that education continues to provide maximum benefits for students. By continuing to improve and develop hybrid learning models, we can prepare future generations to face challenges more prepared and capable.